APPLICATION OF CHAMPOR ON SEVERAL RICE SEED VARIETIES (Oryza sativa L.) AND THEIR EFFECTS ON MORTALITY IN SEED POWDER PESTS (Rizhopertha dominica: Kata kunci: Kapur barus,Varietas, Mortalitas, Rizhopertha dominica - Fendy Nayogi; Suharjono Suharjono (Innofarm:Jurnal Inovasi Pertanian, 2022)
This study aims to determine the effectiveness of champor with the active ingredient Naftalen on pest mortality Rizhopertha dominica seed powder pests and the effect of varieties on the intensity of attacks. The study was conducted using factorial completely randomized design (RAL) with 3 replications and 24 combinations. The first factor is the dose of camphor (C) consisting of 4 levels of C1 = 0 mg / 0.5 kg; C2 = 0.5 mg / 0.5 kg; C3 = 1 mg / 0.5 kg; C4 = 1.5 / 0.5 kg. The second factor is the type of variety (V) with 3 levels, namely V1 = Ciherang; V2 = Sintanur; V3 = Situbagendit. The results of the study, based on analysis of test Annova with the level of 5% stated that the application interaction with varieties of camphor significant effect on mortality Rizhopertha dominica. Further test results Duncan Multiple level of 5%, Aplication of camphor with the highest mortality values on C2 level of 0.5 mg / 0.5 kg of rice seeds was significantly different from the other dose. Varieties significantly affect the intensity of pest attacks warehouse dominica Rizhopertha seed powder, with a low intensity of the attack on the variety of different V3 Situbagendit real Ciherang varieties V1 and V2 Sintanur. Varieties significantly affect the intensity of pest attacks the best combination of each of the first factor and the second factor is Ciherang 0.5 mg / 0.5 kg (C2V1); Sintanur with a dose of 0.5 mg / 0.5 kg (C2V3); Situbagendit at a dose of 1 mg / 0.5 kg (C3V3).